Clumping and Viability of Bone Marrow Derived Mesenchymal Stromal Cells under Different Preparation Procedures: A Flow Cytometry-Based In Vitro Study - Li-li Cui; Tuure Kinnunen; Johannes Boltze; Johanna Nystedt; Jukka Jolkkonen (Stem Cells International)
Complications of microocclusions have been reported after intra-arterial delivery of mesenchymal stromal cells. Hence, quantification and efficient limitation of cell clumps in suspension before transplantation is important to reduce the risk. We used a flow cytometry-based pulse-width assay to assess the effects of different cell suspension concentrations (0.2–2.0 × 106/mL), storage solutions (complete growth medium, Dulbecco’s phosphate-buffered saline, and normal saline), storage time in suspension (0–9 h), and freeze-thawing procedure on the clumping of rat bone marrow derived mesenchymal stromal cells (BMMSCs) and also evaluated cell viability at the same time. Surprisingly, increasing the cell concentration did not result in more cell clumps in vitro. Freshly harvested (fresh) cells in normal saline had significantly fewer cell clumps and also displayed high viability (>90%). A time-dependent reduction in viability was observed for cells in all three storage solutions, without any significant change in the clumping tendency except for cells in medium. Fresh cells were more viable than their frozen-thawed counterparts, and fresh cells in normal saline had fewer cell clumps. In conclusion, cell clumping and viability could be affected by different cell preparation procedures, and quantification of cell clumping can be conducted using the flow cytometry-based pulse-width assay before intra-arterial cell delivery.